Korean media discourse on international education. (8th August 2019) - Yi, Joseph; Jung, Gowoon
ABSTRACT: This paper analyses the representation of international education in the Korean print media, by comparing texts produced by the leading conservative ( Chosun ) and progressive ( Hankyoreh ) newspapers in 1997 and 2014 ( N = 271 articles). We find a major expansion and diversification of media articles on international education, including rising numbers of articles mentioning non-traditional destinations (beyond USA and UK), written or shaped by non-traditional media producers (i.e., educational agents), and including individual-utilitarian and positive themes. We quantify, and find statistically significant correlations among, three key variables (destination, media producer, discourse theme). Articles mentioning non-traditional destinations are more likely to be written or shaped by agents than by journalists only. Articles mentioning non-traditional destinations and articles written or shaped by agents include relatively more positive and individual-utilitarian themes (but not more individual-expressive themes) than do articles not mentioning non-traditional destinations and articles written by journalists only. Theoretically, we link the evolution of media discourse to neo-liberal structural and ideological changes that encourage market competition and consumer choice.